Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.55966/sjarr.2022.3.1.0048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship between Obesity and Life Satisfaction among Male and Female Students of Pakistan

Abstract: The study intends to explore the relationship between Obesity and life satisfaction among male and female students. The sample of present study was 400 comprises of both male and female (200 each) and explored their respective demographics. The study is located at Faisalabad. The Instrument used to access the life satisfaction and Obesity was the life Satisfaction Scale and BMI of the participants respectively.  Data was analyzed using different statistical techniques including repeated measures ANOVA and Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…This study from Pakistan revealed an inverse link between physical extra and student satisfaction in life. It hinted that relational position might intervene in the tie between plumpness and a sense of well-being, as referenced in the source (49) . These discoveries propose that having a companion may be related to a greater risk of weight-related body fat, even though the underlying mechanisms and interactions with other elements, such as origin and education, may be complex and require further exploration.…”
Section: Factors Associated With Obesity According To Each Criterionmentioning
confidence: 99%
“…This study from Pakistan revealed an inverse link between physical extra and student satisfaction in life. It hinted that relational position might intervene in the tie between plumpness and a sense of well-being, as referenced in the source (49) . These discoveries propose that having a companion may be related to a greater risk of weight-related body fat, even though the underlying mechanisms and interactions with other elements, such as origin and education, may be complex and require further exploration.…”
Section: Factors Associated With Obesity According To Each Criterionmentioning
confidence: 99%